Pulses for Sustainability: Breaking Agriculture and Food Sectors Out of Lock-In - Magrini, Marie-Benoit; Anton, Marc; Chardigny, Jean-Michel; Duc, Gerard; Duru, Michel; Jeuffroy, Marie-Helene; Meynard, Jean-Marc; Micard, Valerie; Walrand, Stephane (Frontiers in Sustainable Food Systems, 2018)
Crop diversification can improve the sustainability of Western agriculture. In particular, pulses are crops that can help both agriculture and the food industry more ecological, as they reduce greenhouse gas emissions and offer opportunities to reduce animal-based food consumption. However, the development of those crops in Europe remains locked-in by major crops that have been co-developed to a greater extent both in farming and food systems. After recalling the major mechanisms that lead to this lock-in, this article proposes to adopt a co-evolution framework to tackle with a dual transition of both agriculture and food systems. We question how the current societal trends in the agrifood system offer new opportunities for pulses, and how simultaneous changes both in production and consumption can occur to facilitate this dual transition. Based on various insights from the literature, and some points of views from stakeholders in France - taken here as examples - we argue that to develop pulses, strong support is required from public institutions to coordinate and guide the multiple actors involved in the same direction.